The twelve topsy-turvy, very messy days of Christmas [compact disc, unabridged] - Patterson, James, 1947-; Safran, Tad (Hachette Audio, 2022)
It's mid-December and for the fifth year, at the Sullivans' lonely brownstone in Harlem, stockings go un-stuffed, tinsel un-strewn, gifts un-bought, mistletoe un-hung, chestnuts un-roasted, carols un-played, cookies un-cooked and a tree un-visible. But this year, a mysterious someone is sending gifts to widower Henry Sullivan and his two children, Will and Ella. These gifts are strange. Noisy. And there's no returning them. First, a small beaked and feathered face pokes its head out from between the branches of a pear tree. Within days, the brownstone is full of boisterous animals and house guests all demanding their attention. To the Sullivans, everything about these twelve long, hard, topsy-turvy, very messy days of Christmas are impossible. And impossible may be just the gift their family needs.